Sit tibi terra gravis : sepolture anomale tra età medievale e moderna : atti del Convegno Internazionale di Studi Albenga (SV) - Palazzo Oddo, 14-16 Ottobre 2016 - Pergola, Philippe,; Roascio, Stefano,; Dellù, Elena, (Limina/limites. Archaeologies, histories, islands and borders in the Mediterranean (365-1556) ;, 2023)
The papers in this volume explore the phenomenon of anomalous burials on a European scale, with an interdisciplinary reading between archaeology, history, physical and cultural anthropology.